IMPACT OF THE INTERNET OF THINGS (IOT) ON BUSINESS OPERATIONS AND ASSET MANAGEMENT - Ahmad Nur Budi Utama; Titik Haryanti; Usup (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
Study This aim For study influence the revolution that the Internet of Things (IoT) brings in change operation business and strategy management assets. Through studies the literature is methodically, analyzed how IoT came to be vital instrument for acceleration efficiency operations and improvements management asset data - based. Study elaborate various IoT applications, from maintenance predictive until process automation and monitoring real-ti me assets. Findings show that IoT uses have impact substantial in identify and overcome problem operational, optimizing use source power, as well minimize time dead equipment. Besides that, admittedly exists various related challenges like data security and privacy, which becomes consideration critical in IoT implementation. Studies This provide outlook to ways in which IoT can integrated more Far to in practice business, while highlighting necessity strategy adequate security For protect information obtained. Research is recommended advanced focus on development solution security innovative and evaluating impact social and economic from widespread adoption of IoT wide to power work and society.